Current trends in treasury management: A systematic review - Maria Rosa Tumaya Chaustica; Luis Miguel Romero Echevarria; Fernando Emilio Escudero Vilchez; Silvia Liliana Salazar Llerena; Walter Santamaria Portocarrero; Jose Luis Villegas Chumpitaz; Clefort Bachan Alcantara Cuadrado; Pedro Antonio Arevalo Martinez (International Journal of Medical Toxicology and Legal Medicine, 2024)
Treasury management is a determining function within organizations because financial performance depends on the adequate optimization of the resources available. A systematic review was developed with the objective of identifying the main trends in current treasury management. In this process, the PRISMA methodology was used to carry out a rigorous search for relevant documents, of which 18 articles obtained mainly from Scopus and Scielo were selected. Finally, the importance of treasury management for the execution of other company activities was highlighted, as well as new trends that make use of computer tools, show interest in sustainability, calculate risks through automated processes and use models of simulation.